2016
DOI: 10.3390/met6050114
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Fracture Behavior of Progressively-Drawn Pearlitic Steels

Abstract: Abstract:In this paper a study is presented of the tensile fracture behavior of progressively-drawn pearlitic steels obtained from five different cold-drawing chains, including each drawing step from the initial hot-rolled bar (not cold-drawn at all) to the final commercial product (pre-stressing steel wire). To this end, samples of the different wires were tested up to fracture by means of standard tension tests, and later, all of the fracture surfaces were analyzed by scanning electron microscopy (SEM). Micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…The diameters of the wires E0 and E3 were, respectively, d E0 = 11.03 mm and d E3 = 8.21 mm [32]. Accordingly, the drawing induced engineering plastic strain in the steel E3 is (d which corresponds to the engineering strain of 3.9 (the details of drawing chain behind the present study can be found in the cited paper [32]). Taking into account elevated levels of test load and rather not large wire diameters, undesirable buckling could appear during testing in the compression loading phase.…”
Section: Methodsmentioning
confidence: 64%
See 3 more Smart Citations
“…The diameters of the wires E0 and E3 were, respectively, d E0 = 11.03 mm and d E3 = 8.21 mm [32]. Accordingly, the drawing induced engineering plastic strain in the steel E3 is (d which corresponds to the engineering strain of 3.9 (the details of drawing chain behind the present study can be found in the cited paper [32]). Taking into account elevated levels of test load and rather not large wire diameters, undesirable buckling could appear during testing in the compression loading phase.…”
Section: Methodsmentioning
confidence: 64%
“…To analyse the BE in high strength steels used in civil engineering, various Bauschinger tests were carried out with the steels corresponding to two stages of the industrial seven-step cold drawing process used for obtaining commercial prestressing steel wires: the initial hot rolled bar not yet subjected to drawing to generate plastic strain (i.e., the drawing induced strain is nil there), which is labelled hereafter as the steel E0, and the steel from the intermediate drawing stage after passing through three drawing dies, which is denoted as the steel E3. The diameters of the wires E0 and E3 were, respectively, dE0 = 11.03 mm and dE3 = 8.21 mm [32]. Accordingly, the drawing induced engineering plastic strain in the steel E3 is (dE0 2 /dE3 2 ) − 1 = 0.80, which is rather moderate in comparison with that generated by the industrial drawing process rendering the diameter of manufactured prestressing wire close to 5 mm, which corresponds to the engineering strain of 3.9 (the details of…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This way, loading cycles oscillate between a null stress and a different maximum stress (σ max ) for each case of study. Thus, Load I and Load II applies a maximum load within the material elastic domain (i.e., about 75% and 90% of σ Y = 1300 MPa, 0.002% offset yield strength of a typical prestressing steel used in construction [19]: 1000 and 1200 MPa, respectively). Three additional loading schemes were also considered: a load that reaches the material yield strength at maximum load (Load III), and two loading where the maximum stress overcomes the material yield strength: Load IV, 110% of yield strength (i.e., 1400 MPa) and Load V, 125% of yield strength (i.e., 1600 MPa), respectively.…”
Section: Numerical Modellingmentioning
confidence: 99%